In Vivo Evaluation of Thiamine Hydrochloride with Gastro-Retentive Drug Delivery in Healthy Human Volunteers Using Gamma Scintigraphy - Li-Ying Kam; Jia-Woei Wong; Kah-Hay Yuen (MDPI AG, 2023)
A floating tablet system containing thiamine hydrochloride, a model drug with a narrow absorption window, was evaluated. The tablet was found to have a floating lag time of less than 30 s with a sustained drug release over 12 h during in vitro dissolution studies. The gastro-retentive property of the tablet in relation to the bioavailability of thiamine was determined in healthy human volunteers using gamma scintigraphy under fasted and fed conditions. The gastro-retentive time of the floating tablet could be prolonged up to 10 h under the fed state, compared to about 1.8 h in the fasted state. The prolonged gastric retention under the fed state resulted in a 2.8-fold increase in oral bioavailability of thiamine compared to that of the fasted state. There was also a 1.4-fold increase in thiamine absorption compared to that of a conventional immediate release tablet in the fed state. In the fasted state, the extent of thiamine absorption from the floating tablet was only about 70% of that absorbed from the immediate release tablet. Thus, to achieve a better performance, such floating tablet systems should be administered under a fed condition, to prolong the gastric retention time.